Анализ финансово-хозяйственной деятельности: Учебник / Л. Н.Чечевицына, И. Н.Чуев - Чечевицына Людмила Николаевна (Маркетинг, 2002)
Экземпляры: (20160328) / Инвентарный номер: 36993 / Цена: / Сис.шифр: 65.053 / Авт.знак: Ч57 / ГРНТИ: 10.21.21 / ББК: 65.053 я73